Design, Analysis and Fabrication of Hydraulic Scrap Baling Machine - Kumbhar, S. V.; Jadhav, M. A.; Husainy, Avesahemad; S. G. Bardiya; Patil, Omkar B.; Mali, Shubham K. (Asian Review of Mechanical Engineering, 2019)
There are several industrial production processes that involve mechanical machining of cast parts by various operations such as turning, milling, and drilling. Metal Chips, especially of aluminum, mild steel and cold-rolled carbon steel, etc. The collection, storage, and transportation of metal chips are an important aspect in the process of recycling. This project focuses on the compaction and creation of metal chips bales for ease of storage as well as handling and transportation of metal chips. Efforts have been taken to ensure an efficient waste management system in shop floors, with minimum use of space and energy when it comes to disposing of metal chips formed during machining processes. The large space required to store the chips as loose chips have a large surface area. The scope of the project is limited to the design, analysis, and fabrication of scrap baling machine. A Baling press machine is a machine in which a loose scrap is converted into in the form of 8-12 kg bundle. In this machine, we adopt a square bundle rather than circular shape and square bales acquire less space as compared to the round bales.